Capital and Strengthening of Generation Z Students' Spirituality in the Society 5.0 Era - Rochanah, Rochanah; Masturin, Masturin; Said, Nur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This article aims to determine the capital owned by Generation Z and the efforts to strengthen spirituality that are carried out so that Generation Z is ready to face the era of society 5.0. The locus of this research is at Madrasah Aliyah Negeri Insan Cendekia Pasuruan, East Java, Indonesia. The approach used in this study is qualitative research. The data collection technique chosen was through interviews with MAN Insan Cendekia teachers and seven MAN Insan Cendekia students. The data sources in this study were nine, including Mr. S as the dormitory supervisor, Mrs. Y as the guidance counselor, ODP, NES, SH, ZRMH, IILL, SRB, and KD as students of MAN IC Pasuruan. Other techniques used are observation and documentation. Explicitly, the problems that researchers raise in this study are: what are the capitals owned by Generation Z MAN Insan Cendekia in facing the Era of Society 5.0, and how to strengthen spirituality so that Generation Z is ready to face the era of society 5.0. Data analysis techniques are carried out through data reduction, data presentation, and verification. The results of the study show that the capital owned by Generation Z MAN Insan Cendekia in facing the Era of Society 5.0 includes economic, intellectual, and cultural capital, and efforts to strengthen spirituality are carried out so that Generation Z is ready to face the era of society 5.0. carried out through the study of the Qur'an, secondly, the Study of the Hadith of al-Arba'in an-Nawawiyyah, third, Qiyamull lail every night (Tahajud prayer), fourth, Diba'an.